GENDER DIFFERENCES IN MATHEMATICS ATTITUDES: SELF-CONFIDENCE, ENJOYMENT, AND PERCEIVED VALUE AMONG COMPUTER SCIENCE STUDENTS - Nayan, Asmahani; Zakaria, Shahida Farhan; Bosli, Fazillah (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study investigates gender differences in attitudes toward mathematics among first-year Computer Science (CS) students, focusing on three key dimensions: self-confidence, enjoyment, and value. Understanding students’ affective orientations toward mathematics is crucial, as these attitudes can influence their engagement, persistence, and performance in mathematics-related courses. The study aims to determine whether male and female students differ significantly in their levels of self-confidence, the value they place on mathematics, and the degree of enjoyment they derive from the subject. A total of 114 first-year CS students participated in the study and completed a structured questionnaire designed to measure the three attitude dimensions. The instrument’s reliability was confirmed through internal consistency analysis, while the Mann–Whitney U test was employed to assess gender differences in the responses. The findings revealed no statistically significant gender differences in self-confidence and enjoyment, suggesting that male and female students hold similar levels of belief in their mathematical abilities and experience comparable levels of positive affect toward the subject. However, the analysis identified a small but significant difference in perceived value, with female students reporting a stronger recognition of mathematics as valuable in their academic and professional pursuits than their male counterparts. These results suggest that while self-confidence and enjoyment in mathematics appear unaffected by gender among CS students, female students may place greater importance on the role of mathematics in their studies and future careers. The study contributes to the growing body of literature on gender and mathematics attitudes, highlighting the need for educators to acknowledge and leverage these perceptions to foster equitable and supportive learning environments.